Laboratory analogue of a supersonic accretion column in a binary star system. - Cross, J; Gregori, G; Foster, J; Graham, P; Bonnet-Bidaud, J; Busschaert, C; Charpentier, N; Danson, C; Doyle, H; Drake, R; Fyrth, J; Gumbrell, E; et al. (Nature Publishing Group, 2016)
Astrophysical flows exhibit rich behaviour resulting from the interplay of different forms of energy-gravitational, thermal, magnetic and radiative. For magnetic cataclysmic variable stars, material from a late, main sequence star is pulled onto a highly magnetized (B>10 MG) white dwarf. The magnetic field is sufficiently large to direct the flow as an accretion column onto the poles of the white dwarf, a star subclass known as AM Herculis. A stationary radiative shock is expected to form 100-1,000 km above the surface of the white dwarf, far too small to be resolved with current telescopes. Here we report the results of a laboratory experiment showing the evolution of a reverse shock when both ionization and radiative losses are important. We find that the stand-off position of the shock agrees with radiation hydrodynamic simulations and is consistent, when scaled to AM Herculis star systems, with theoretical predictions.